Articulatory speech measures can be related to the severity of multiple sclerosis - Kieling, Maiara Laís Mallmann; Finkelsztejn, Alessandro; Konzen, Viviana Regina; dos Santos, Vanessa Brzoskowski; Ayres, Annelise; Klein, Iasmin; Rothe-Neves, Rui; Olchik, Maira Rozenfeld (Frontiers in Neurology, 2023)
23. Background: Dysarthria is one of the most frequent communication disorders in patients with Multiple 24. Sclerosis (MS), with an estimated prevalence of around 50%. However, it is not clear if there is a 25. relationship between dysarthria and the severity or duration of the disease. Objective: Describe the 26. speech pattern in MS, correlate with clinical data, and compare with controls. Methods: A group 27. of MS patients (n=73) was matched to healthy controls (n=37) by sex and age. Individuals with 28. neurological and/or systemic conditions that could interfere with the speech were excluded. MS group 29. clinical data were obtained through the analysis of medical records. The speech assessment consisted 30. of auditory- perceptual and speech acoustic analysis, from recording the following speech tasks: 31. phonation and breathing (sustained vowel /a/); prosody (sentences with different intonation patterns) 32. and articulation (diadochokinesis; spontaneous speech; diphthong /iu/ repeatedly). Results: In MS, 33. 72.6% of the individuals presented mild dysarthria, with alterations in speech subsystems: phonation, 34. breathing, resonance, and articulation. In the acoustic analysis, individuals with MS were significantly 35. worse than the control group (CG) in the variables: standard deviation of the fundamental frequency 36. (p=0.001) and maximum phonation time (p=0.041). In diadochokinesis, individuals with MS had a 37. lower number of syllables, duration, and phonation time, and in spontaneous speech, a high number of 38. pauses were evidenced as compared to CG. Correlations were found between phonation time in 39. spontaneous speech and the Expanded Disability Status Scale (EDSS) (r=- 0.238, p=0.043) and 40. phonation ratio in spontaneous speech and EDSS (r=-0.265, p=0.023), which indicates a correlation 41. between the number of pauses during spontaneous speech and the severity of the disease. 42. Conclusions: The speech profile in MS patients was mild dysarthria, with decline in the phonatory, 43. respiratory, resonant, and articulatory subsystems of speech, respectively, in order of prevalence. The 44. increased number of pauses during speech and lower rates of phonation ratio can reflect the severity of 45. MS.